ANALISIS FLUKTUASI DOLLAR AMERIKA SERIKAT TERHADAP RUPIAH DI SAAT DAN SETELAH KRISIS SUBPRIME MORTGAGE 2007 - 2013 - Gustiyan Taufik Mahardika; Hermanto Siregar; Dedi Budiman Hakim (Signifikan: Jurnal Ilmu Ekonomi, 2014)
In a floating system, exchange rates fluctuate due to macroeconomic conditions that occur. Due to the uncertainty caused by economic shocks or financial crises such as subprime mortgage crisis, fluctuation analysis can be used to minimize the risks that arise in business that involve exchange rates such as export/import or hedge funds. This study aims to analyze the fluctuations in the exchange rate during and after the subprime mortgage crisis 2007 – 2013 in order to give a better understanding on the dynamics of the exchange rate. By analyzing the dynamics, individuals or companies that make the currency as a component in its business can then decide the right policy to implement. Analyses were performed using an error correction model (ECM) for nominal (NER) and real exchange rate (RER). The variables that are proven significant for NER are money supply (JUB), current account (CAB), economic growth (EGROW), and the nominal central bank rate (NBIRATE). The dummy crisis variable did not have a significant effect on the NER, while the CAB affect NER in the short run only, and EGROW affect NER in the long run only.DOI: 10.15408/sjie.v3i2.2060